Combining geological surveys, sizing tools and 3D multiphysics in designing a low temperature district heating with integrated ground source heat pumps. (May 2022) - Viesi, Diego; Galgaro, Antonio; Dalla Santa, Giorgia; Di Sipio, Eloisa; Garbari, Tomas; Visintainer, Paola; Zanetti, Alberto; Sassi, Raffaele; Crema, Luigi
Highlights: A 3-step design for shallow geothermal DH is evaluated in a real case study. Step 1: geological, hydrogeological and thermophysical parameters are investigated. Step 2: sizing tools identify the necessary groundwater flow rate and BHEs length. Step 3: 3D multiphysics modeling evaluates the induced thermal plume. Relevant scientific novelty in the multi-scale and multi-method geological surveys. Abstract: Shallow geothermal energy has the potential to play a crucial role in future renewable district heating and cooling networks. However, to size, model and design such systems, an accurate underground survey campaign is necessary, providing on-site geological, hydrogeological and thermophysical parameters. This is particularly true in geologically complex environments such as mountain ones. This paper presents a real case study located at the Madonna Bianca neighborhood in the city of Trento (North Italy, in an alpine valley), where a comprehensive geological survey campaign has been conducted by using traditional and innovative techniques, in order to size a low temperature district heating with integrated ground source heat pumps, also evaluating its thermal effects on the underground by using a 3D hydro-thermal finite element modeling (FEM). Relevant scientific novelty is included in the multi-scale and multi-method geological surveys, coupling: on-site coring, surface and downhole geophysics, laboratory petrophysical analyses, on-site thermal response tests (TRTs) by standard device and by novel hybrid optical fiber. The proposed framework is replicable and supports not only the correct plant dimensioning but also the evaluation of energy-efficiency and energy-sustainability over time.